Presenting "The Other Half": Jacob Riis's Reform Photography and Magic Lantern Spectacles as the Beginning of Documentary Film. Issue 2 (3rd April 2019) - Yotova, Denitsa
Abstract : This article examines the emergence of the visual documentary genre through the study of Jacob A. Riis's magic lantern spectacles, writings, photographs, audience reception, and critical reviews as published in the press during the late 19th and early 20th centuries. To demonstrate an existing strong connection between Riis's lectures and documentary film, in particular, the article also focuses on a more contemporary idea about documenting society—the concept of documentary modes of representation. The analysis of related primary and secondary sources reveals that despite the limitations of technology, "moving" documentary pictures were produced long before they were part of the film genre, and Riis's work should be viewed as one of the principal antecedents to this visual documentary form.